POLITENESS STRATEGIES IN DRUMLINE MOVIE - ADITYA, IGNATIUS ANDRA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: politeness strategies, movie, DrumlinePoliteness strategies use in communication between speaker and hearer has power tomaintain relationship, and decrease the threatening face and message that happens during the interaction. That became the point of departure in this study, in which politeness strategies were used to analyze the characters’ relationship development in a Drumline movie. The purpose of this study were (1) to identify type of negative and positive politeness strategies used by the character for the communication, and (2) to find out characters’ relationship development influenced by the politeness strategies.To answer those questions, Brown & Levinson’s politeness strategies were used as thetheoretical framework, and the research design was descriptive qualitative. Data collection was done through watching movie, classifying politeness strategies, and analyzing the classification.The result showed the Drumline’s characters tend to use negative politeness ratherthan the positive. It reveals that there were 28 data containing politeness strategies, they are 20 negative politeness strategies and 8 positive politeness strategies. At the beginning the characters mostly use positive politeness as introduction or as a socialization starting point, then they frequently use negative politeness strategy to maintain their relationship and it also triggers the character relationship development.This research is expected to contribute to the body of knowledge related to theapplication of Brown & Levinson’s politeness strategy which is used in the movie. It isalso suggested that the next researchers who want to conduct research in politeness strategy use other types of theory for example Leech or Folley, and apply it to other object of the study such as speech, novel, short story, etc. Thus, there will be more variation and knowledge sources related to politeness strategy.